2013
DOI: 10.14210/bjast.v17n1.p35-41
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Two Household Liquid Soaps on Poecilia reticulata Peters, 1859

Abstract: (MFLS) were evaluated for the Poecilia reticulata in laboratory bioassays. The acute toxicity was evaluated for 96 h while the sub-lethal effects of the two surfactants on the biochemical parameters of P. reticulata were investigated for a 6 -day exposure period. The derived toxicity indices showed that the FLS (96hLC 50 = 0.062ml/L) was 1.37 times more toxic than the MFLS (96hLC 50 = 0.085ml/L) against P. reticulata. Analysis of variance (ANOVA) showed signifi cant difference (p<0.05) in the quantal response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
4
2
0
1
Order By: Relevance
“…The toxicity of the detergents on the test fingerlings were concentration dependent, and this corroborated with the report of [18]. In the present study, it was observed that the 96h LC 50 value were 5.45 and 5.60 ppm for Zip and Omo detergent respectively and similar values were reported by [19,15]. The 96h LC 50 value of Zip detergent was slightly lower than that of Omo, and this denotes that the Zip detergent is slightly more toxic than Omo detergent.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The toxicity of the detergents on the test fingerlings were concentration dependent, and this corroborated with the report of [18]. In the present study, it was observed that the 96h LC 50 value were 5.45 and 5.60 ppm for Zip and Omo detergent respectively and similar values were reported by [19,15]. The 96h LC 50 value of Zip detergent was slightly lower than that of Omo, and this denotes that the Zip detergent is slightly more toxic than Omo detergent.…”
Section: Discussionsupporting
confidence: 93%
“…Similar observations were reported by [21,22,23,1,19,15,9]. This behavioural abnormalities could be due to nervous and respiratory impairment as a result of blockage of nervous transmission between the nervous systems and various effectors sites, enzyme dysfunctions that may induce paralysis of respiratory muscles and/or depression of respiratory center and disturbances in energy or metabolic pathways which results in depletion of energy [19]. The gills of the control group did not show any recognizable changes and consisted of primary filament and secondary lamellae which agrees with findings of [17] for C. gariepinus exposed to lethal and sub-lethal concentration of soap and detergents.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As atividades humanas têm ocasionado uma série de impactos sobre estes sistemas como supressão de mata ciliar (Dosskey et al, 2010), eutrofização das águas devido ao aporte excessivo de nutrientes provenientes principalmente de atividades agropecuárias (Monteagudo et al, 2012;Pedrazzi et al, 2013;Smith et al, 2013) e despejo de efluentes (Thevenon et al, 2011;Lawal et al, 2013), alterações do regime hídrico (Costigan & Daniels, 2012), poluição por metais pesados (Thevenon et al, 2011;Medeiros et al, 2013) e agrotóxicos (Moreira et al, 2012), introdução de espécies exóticas (Sousa et al, 2008) e assoreamento (Melo et al, 2004).…”
Section: Introductionunclassified